Prune-belly syndrome associated with extra-abdominal abnormalities in a 7-year-old boy - Kabakuş, Nimet; Serhatlıoğlu, Selami; Akfırat, Murat; Kazez, Ahmet; Aydınoğlu, Hakan; Özercan, İbrahim; Aygün, A. Denizmen (The Turkish Journal of Pediatrics, 2000)
Prune-belly syndrome (PBS) is an association of abdominal wall deficiency, genitourinary anomalies, and in males, cryptorchidism. Other congenital anomalies are associated with PBS, particularly musculoskeletal deformities and gastrointestinal tract anomalies. In this report, a seven-year-old boy with PBS had mega cisterna magna variant, microcornea, aortic stenosis with bicuspid aortic valves, cholelithiasis, and Hirschsprung’s disease. Coexistence of these abnormalities with PBS supports the concept of PBS being caused by an early disturbance of not only mesodermal development but also of the other germ layers. There was maternal ingestion of drugs in the 1st month of gestation. All cases with PBS should be evaluated thoroughly for extra-abdominal abnormalities resulting from disturbances of ectodermal and endodermal development. Even though disturbances related to ectodermal and endodermal development may be asymptomatic, early diagnosis of the disturbances may help in preventing possible future problems.
Keywords: prune-belly syndrome; microcornea; aortic valve stenosis; bicuspid aortic valve; cholelithiasis; Hirschsprung’s disease; mega cisterna magna variant